Teaching historical pandemics, using Bernstein’s pedagogical device as framework (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
On 11 March 2020, the World Health Organisation (WHO) declared COVID-19 a global pandemic. This announcement came as a shock to countries around the world. Diverse responses across the globe exposed an ill-prepared world that lacks the historical consciousness and capacity to manage and fight off a global pandemic. Mitigation of COVID-19 requires, inter alia, knowledge of best practices, in which case memory of the 1918 Spanish Flu pandemic comes to mind. This event claimed the lives of 50 million people,1 which is more than the number of people who died during the two 20th century world wars. Responding to the arguably poor historical knowledge of pandemics, this article presents an exploratory proposal to integrate historical knowledge of pandemics with History teaching at school. Considering Bernstein’s pedagogical device as a conceptual framework, the article responds to the question: how can historical knowledge of pandemics be integrated with History teaching? A small qualitative sample of online responses from History teachers (N=15) was used to gather a sense of how practicing History teachers relate to historical pandemics in the context of COVID-19. Their responses assisted in opening a discussion around knowledge production, recontexualisation and reproduction during the design process. Based on the expectation that knowledge of pandemics will be taught in the history classroom, recommendations for teacher education are suggested.
Keywords: COVID-19; History teaching; Knowledge production; Pandemic; Pedagogical device; Recontextualisation; Reproduction